Reduced muscle strength of knee extensors is a risk factor for silent lacunar infarcts among Japanese elderly people: the Bunkyo Health Study. Issue 3 (28th June 2020) - Someya, Yuki; Tamura, Yoshifumi; Kaga, Hideyoshi; Sugimoto, Daisuke; Kadowaki, Satoshi; Suzuki, Ruriko; Aoki, Shigeki; Hattori, Nobutaka; Motoi, Yumiko; Shimada, Kazunori; Daida, Hiroyuki; Ishijima, Muneaki; et al.
Abstract: Background: Silent lacunar infarcts (SLIs) are often incidentally diagnosed by brain magnetic resonance imaging in elderly people and are associated with the future onset of stroke, dementia, and frailty. While decreased muscle strength was reported as a risk factor for stroke, it is still unclear whether it also predisposes to SLI. In this study, we investigated the association between muscle strength and SLI in elderly subjects. Methods: The subjects were 1536 elderly people aged 65–84 years without previous stroke events, living in an urban area of Tokyo, Japan, and recruited in the Bunkyo Health Study. Lacunar infarcts were defined by brain magnetic resonance imaging. Muscle strength of the knee extensors was measured using a dynamometer. After categorizing subjects by age and sex, we divided them into three groups based on muscle strength tertiles (High, Medium, and Low) and investigated the association between muscle strength and SLI. Results: The mean subject age was 73.0 ± 5.4 years, and 58.9% were female. The prevalence of SLI was 16.4% and was inversely associated with muscle strength (High, 12.3%; Medium, 17.7%; and Low, 19.3%; P for trend 0.003). After multivariate adjustment, the odds ratio for SLI was increased in the Medium and Low groups compared with the High group (High, 1.00 [reference]; Medium, 1.42 [95% confidence interval: 0.98–2.04]; and Low: 1.48 [1.02–2.14]), and the linear trend across the three groups was significant ( P for trend 0.043). Conclusions: Reduced knee extensor muscle strength is associated with SLI among Japanese elderly, independently of other established risk factors.